A violência intrafamiliar contra crianças e adolescentes e sua superação a partir do acionamento da rede de apoio social e afetiva - Lira, Margaret Olinda de Souza Carvalho e (2010)
Overcome intrafamiliar violence situations constitute a big challenge to the involved families, needing for this, support and orientation guaranteed by a social and personal structure which will the individuals belong. The study investigated the violence phenomenon against children and adolescents practiced by their families, in a perspective of studying the overcoming process of this practice, understanding the family resilience process where ocurred intrafamiliar violence episodes against their children on the city of Petrolina by the Tutelar Council actuation and by the institutions that integrate the social and afective support net. The family characterization was build through the treatment charts documental analisys, by the Tutelar Council. Towards the participation assesment of the social and afective support-net, was used the Bardin's case study and content analisys, by 5 categories establishment: familiar relationship, experience with intrafamiliar violence, meanings of intrafamiliar violence and overcoming mechanisms. Of the 432 violence cases registered, the mother leads as the violence author practiced against children (51%), being a negligence predominane (77,08%) comparing with other types of violence. This modality was the one with biggest ocurrence percentual, reachind children between 11 and 15 years old in 31,67% of the cases. The children that suffered more violence in this study was the females (55,15%). The main justification presented by families to the overcoming wah de support received by their afective net, formed by familiars and friends. We consider the research relevant, not simply for support the comprehension of this practice frequently present in the intrafamiliar relationship, but, especially for enlarge subsidies to the reader, able to demystify distorted visions whose show only the intrafamiliar violence from parents against children without demonstrate overcoming alternatives. It's expected, thus, to provide elements to upgrade the support net to the families in intrafamiliar violence situations at Petrolina, contributing to the affront and the overcoming of this violence, helping to prevent recurrences. The community's elucidation and the capacity of the professionals that integrate this service will contribute to the chidren and adolescent rights' effectuation, by the execution of prevention actions, and reduction of the intrafamiliar violence cases by the correct treatment to the involved (victims and family).